2015
DOI: 10.1111/ajsp.12101
|View full text |Cite
|
Sign up to set email alerts
|

Social exclusion influences attentional bias to social information

Abstract: Using three experiments, the present study investigates the impact of social exclusion on attention. Specifically, we investigate whether social exclusion promotes attentional bias to social acceptance cues (smiling faces) or social exclusion cues (angry faces) among an Asian population. The Cyberball game was adopted to manipulate social inclusion or exclusion, and a dot-probe task was used to measure individuals' responses to smiling or angry faces. In Experiments 1 and 2, each trial consisted of either a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Cacioppo & Hawkley, ). Attending to affiliative cues might help them pick out the most likely sources of reinclusion (DeWall, Maner, & Rouby, ), or attenuate the negative feelings elicited by exclusion (Xu et al ., ; although see Syrjämäki, Lyyra, Peltola, & Hietanen, ). Individual differences and situational factors might determine which coping strategies individuals utilize as a response to different kinds of exclusion experiences, explaining why exclusion influences attention differently in different individuals (Tanaka & Ikegami, ; Tuscherer et al ., ).…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 99%
See 2 more Smart Citations
“…Cacioppo & Hawkley, ). Attending to affiliative cues might help them pick out the most likely sources of reinclusion (DeWall, Maner, & Rouby, ), or attenuate the negative feelings elicited by exclusion (Xu et al ., ; although see Syrjämäki, Lyyra, Peltola, & Hietanen, ). Individual differences and situational factors might determine which coping strategies individuals utilize as a response to different kinds of exclusion experiences, explaining why exclusion influences attention differently in different individuals (Tanaka & Ikegami, ; Tuscherer et al ., ).…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 99%
“…Xu et al . (, Experiments 2–3) found that excluded, but not included, participants showed an attentional bias to smiling faces as early as 200 ms after presenting the stimuli in a dot‐probe task. This is interesting, as people may be unable to voluntarily shift the locus of attention this fast (Johnson, ).…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 99%
See 1 more Smart Citation
“…Other research manifested that social exclusion, which generates social pain, may bias interpersonal perception. Being socially rejected leads to selective attention to smiling faces (DeWall, Maner, & Rouby, ), more positive impressions of new social targets, except those who caused the exclusion (Maner, DeWall, Baumeister, & Schaller, ), biased attention to social information (Xu et al ., ), and hostile perception of ambiguous others (DeWall, Twenge, Gitter, & Baumeister, ). Another branch of research confirmed that some physical factors also could change the way people perceive others.…”
Section: Pain and Negative Interpersonal Perceptionmentioning
confidence: 99%
“…In our daily life, facial expressions can serve as social communicative signals to allow us to better estimate a person's motivational state (Xu et al, 2015). The N170 component, which is shown in the temporo-occipital areas approximately 170 ms after the onset of a face stimulus, has been shown to be sensitive to facial stimuli (Bentin et al, 1996) and emotional facial expression (Schupp et al, 2004).…”
Section: Introductionmentioning
confidence: 99%